NEBULAR TURBULENCE, CHONDRULE FORMATION, AND THE COMPOSITION OF THE EARTH - Hewins R.H.; Herzberg C.T. (My University, 1996)
Cosmochemical fractionations have been traditionally explained by the segregation of fine condensate dust, yet nebular turbulence prevents this dust from separating from the gas. Dense chondrules may form accumulations in stagnant zones which can settle to the midplane and be accreted to planetesimals and terrestrial planets. This is supported by the observation that Type I (MgO-rich) chondrules are more similar to mantle periodotite from Earth in lithophile major and trace element abundances than bulk chondrites are.
Keywords: COSMOCHEMISTRY; CHONDRULES; CHEMICAL FRACTIONATION; TERRESTRIAL COMPARISON